Vaccination Policies and Public Health Resilience: A Normative Analysis Based on WHO and UNICEF Reports - Nisrina Fakhiroh Hidayati Nublah; Vindi Tyastutik (Hippocratica : Journal of Modern Medicine and Healthcare Practice, 2026)
Vaccination systems have increasingly been recognized as central components of resilient public health governance, particularly following disruptions caused by global health emergencies. This study examines how vaccination policies are normatively framed as instruments of health system resilience within major international institutional guidance. Using a non-empirical qualitative document analysis, the research systematically reviews strategic and operational reports issued by the World Health Organization and UNICEF, applying thematic coding and interpretive synthesis to identify underlying ethical assumptions, governance logics, and institutional priorities. The findings indicate that global vaccination discourse constructs resilience as a multidimensional governance objective shaped by equity commitments, institutional integration, sustainable financing, and public legitimacy rather than by epidemiological performance alone. Policy frameworks consistently portray immunization as a stabilizing infrastructure capable of sustaining service continuity, reinforcing trust, and supporting long-term development goals. The study concludes that resilient vaccination systems depend on policy coherence, inclusive governance, and durable investment structures that embed immunization within broader health and social systems. These insights contribute to global health scholarship by refining conceptual understanding of vaccination resilience and by demonstrating the analytical potential of normative policy interpretation for evaluating international public health strategies.